Tolerance and effectiveness of nivolumab after pediatric T‐cell replete, haploidentical, bone marrow transplantation: A case report. Issue 3 (21st September 2016) - Shad, Aziza T.; Huo, Jeffrey S.; Darcy, Courtney; Abu‐Ghosh, Amal; Esposito, Giuseppe; Holuba, Mary‐Jo; Robey, Nancy; Cooke, Kenneth R.; Symons, Heather J.; Chen, Allen R.; Llosa, Nicolas J.
Abstract: To date, there has been a lack of pediatric experience regarding the efficacy and tolerability of immune checkpoint inhibitors after haploidentical hematopoietic stem cell transplant (HSCT). We present the case of a 22‐year‐old female with multiple‐relapsed Hodgkin lymphoma (HL) who presented with a new relapse after haploidentical (post‐haplo) HSCT. Anti‐PD‐1 therapy with nivolumab resulted in significant objective disease response and clinical improvement without notable side effects, including the absence of a graft‐versus‐host disease (GVHD). This case report suggests that immune checkpoint inhibition may be safely tolerated even in the setting of haploidentical HSCT, without triggering overt GVHD.